Microwave-assisted synthesis of reduced graphene oxide and vanadium pentoxide hybrid materials for enhanced performance in next generation batteries - LeBan, Levon Aldon II (Kansas State University, 2020)
In a world of increasing energy demands, the need for possible alternatives to lithium in electrical energy storage systems (EES) grows. This opens up the door to the utilization of divalent ion systems (Zn²⁺ and Mg²⁺). Magnesium has the specific advantage of possessing high abundance in the earth’s crust (2.1%), higher volumetric capacity (3833 mAh/cm³ vs. 2046 mAh/cm³), and safer operation due to the lack of dendrite formation during cycling. Zinc also possesses a higher volumetric capacity (5854 mAh/cm³ vs 2046 mAh/cm³), and can be constructed using aqueous electrolytes. The divalent nature of magnesium & zinc ions is also a disadvantage, as ions diffuse significantly more slowly than lithium ions. Hydrated V₂O₅ is expected to help address this issue due to its open structure and large interlayer distance. In addition, water within the crystal structure helps to shield the positive charge of divalent ions as they diffuse into the host material. The low V₂O₅ conductivity can be improved via forming a hybrid material with a conductive carbon template. This was achieved using microwave-assisted synthesis with the vanadium (V) oxytrisisopropoxide (VTIP), H₂O, and graphene oxide (GO) to create a hybrid structure of hydrated V₂O₅ on the reduced graphene oxide (rGO). Microwave-assisted synthesis enables fast specific heating, reaching an elevated temperature (180 C˚) and pressure (15 bar) similar to a hydrothermal reaction. This was followed by an annealing step that allows for controlling the degree of hydrations and study its effect on the electrochemical performance. Materials characterization using thermogravimetric analysis (TGA), Raman spectroscopy, scanning electron microscopy (SEM), x-ray diffraction (XRD), X-ray photo electron spectroscopy (XPS) and transmission electron microscopy (TEM) has revealed that the hydrated V₂O₅ has been successfully deposited on the rGO surface, forming a strongly attached hybrid material. Electrochemical tests show that the material can function as a cathode for 2 and 3 lithium insertion, at C/9, C/6, C/3 and C rates, achieving the theoretical capacity (294 mAh/g for 2 Li⁺ processes) at C/9 and maintaining a good coulombic efficiency (>98%). Increasing the current rate in this and all subsequent cell conditions decreases the capacity. The initial magnesium cells are found to perform poorly, suffering from the poor stability and low reversibility, mainly limited by the low Mg²⁺ ion conductivity across the compact solid electrolyte interface (SEI). By preforming a lithium-salt-containing SEI layer in a Li-ion battery and then using it as the magnesium anode was found to overcome the limitation by the Mg anode and allow the observation of the properties of the cathode based on the hybrid material. Magnesium insertion at C/8, C/4, C/2, and C rate exhibits a peak capacity of 165 mAh/g (0.56 moles Mg insertion) at C/8 and maintains good coulombic efficiency (~95%). The material shows promise for Zinc ion cells, at C, 2C, 4C, and 8C, achieving a high capacity of 410 mAh/g (1.39 moles Zn insertion) at 1C while maintaining a high coulombic efficiency (>98%).
Keywords: Microwave Synthesis; Hydrated Vanadium Pentoxide; Lithium ion cells; Divalent ion cells